A hospital-based study of severe anemia in adults in Eastern India - Dash, Subhash C.; Sundaray, Naba K.; Tudu, Promod K.; Rajesh, Beeravelli (International Journal of Research in Medical Sciences, 2018)
Background: Anemia remains a crucial health problem in developing countries. Cardiac compromise and fatal complications usually occur at Hb of <5g/dL. The aim of the study was to determine possible etiologic and clinical profile in adult patients with very severe anemia (Hb of <5g/dL). Methods: A prospective observational study was conducted in a teaching hospital of Odisha over a period of 12months. A total of 70 patients of both men and non-pregnant women admitted to the medicine wards were included after exclusion. Detailed history, clinical examination and investigation findings were recorded. Independent ‘t’ test, Wilcoxon rank sum test, Pearson chi-square test and Fisher exact test were used as applicable, to compare the variables. Results: The mean Hb (g/dL) was 3.73 ±0.85 and the mean age of the study group was 53.34±17.75years. No significant difference was observed in the severity of anemia between the female (mean Hb of 3.56±0.93) and male patients (mean Hb of 3.87±0.77) (p=0.130). The most frequent etiology found was absolute iron deficiency (44.3%, n=31) and mostly (41.9%) found in the age group of ≥65years (p<0.001). Congestive cardiac failure was found in 20% (n=14) of patients and majority of patients (64.2%, n=9) were males (p<0.001). Conclusions: Iron deficiency is the principal cause of very severe anemia in adults rather than malignancy or anemia of chronic disease and only about one fourth of patients develop heart failure even with very severe anemia.